Ismael's ghosts [videorecording (DVD)] - Amalric, Mathieu, 1965-; Cotillard, Marion, 1975-; Gainsbourg, Charlotte, 1971- (Magnolia Home Entertainment, 2018)
Twenty-one years ago, she ran away, And twenty-one years later, Carlotta is back from the void. But, Ismael has been busy rebuilding a life for himself with Sylvia and working on his next feature film. As Ismael's trials and tribulation unfurl, so too do those of his film's protagonist: idle, funny and reckless diplomat Ivan Dedalus. The character is a nod to the ghost of another of Desplechin's creations.